Impact of Fiber Geometry on the Workability of Refractory Concrete: A Systematic Literature Review - Cano Condori, Harold (LACCEI, 2025)
This literature review aims to determine the influence of the characteristics of fibers added to concrete mixtures designed to withstand high temperatures. Information was gathered from 20 articles published in English between 2018 and 2025 in the Scopus and ScienceDirect databases, following the PRISMA methodology. The main fiber characteristics considered were material, length, diameter, and the amount of fiber added. It was found that the most commonly used standards for evaluating workability are ASTM and BS-EN. Additionally, it was determined that longer fibers with smaller diameters contribute to a decrease in workability. Finally, it was verified that higher percentages of fiber in the concrete mix have a detrimental effect on its workability.